Description of a new species of the genus Chaetostoma from the Orinoco River drainage with comments on Chaetostoma milesi Fowler, 1941 (Siluriformes: Loricariidae) - Ballen, Gustavo A.; Urbano-Bonilla, Alexander; Maldonado-Ocampo, Javier A. (Zootaxa, 2016)
Chaetostoma joropo n. sp. is described from the piedmont of the Orinoco River drainage in Colombia. The new species has been long confused with Chaetostoma milesi, a species with similar overall morphology and color pattern that is restricted to the Magdalena-Cauca River Basin. We diagnose the new species on the basis of morphology as well as a precise description of the color pattern. Chaetostoma joropo n. sp. is also easily distinguished from C. formosae the most similar species and other species inhabiting the Orinoco River drainage in Colombia. Data on ontogenetic variation and sexual dimorphism are provided, as well as natural history notes and remarks on the usage of the name Chaetostoma milesi for specimens from both the Orinoco and Magdalena-Cauca drainages. A discussion on the usage of the name Chaetostoma platyrhynchus is also provided given its current instability in the literature.